Learner-Users Perceptions: Language Learning Affordances and Limitations of Social Networking Tools - Ibrahim, Che Wan Ida Rahimah Bt. Che Wan (International Journal of Asian Social Science, 2018)
Social networking tools are becoming vital tools in young learner’s life. This article attempts to provide a review of the relevant literature in relation to current perceptions among learner-users in terms of the potential benefits and limitations of these tools for their informal language learning. It is important to understand how these applications have led to new innovations for virtual communal experiences. This article provides a more complete representation of the potential advantages and obstacles of these new practices of informal language learning. As presented, the social networking tools have many potentials for efficient language learning development, especially beyond the classroom. These tools are favored by language learner mainly for their online identities formation, their daily practice and trial of informal language learning, with regard to the improvement of both collective and individual learning. The article also shows that the perceived limitations are concerned with the aspects that might be discovered as a constraint, barrier or visual anxiety, but which can offer complementary and equally crucial opportunities for enhancing the informal learning among language learners.